Design and implementation of a PV-tied effective inverter with high reliability and low THD for distribution-grid applications - Nyamathulla, Shaik; C., Dhanamjayulu (Frontiers in Energy Research, 2024)
Research has focused on multilevel inverters (MLIs) due to their use in electric vehicles, renewable energy systems, and industrial applications. This paper proposes a new design for a single-phase 21-level asymmetrical MLI for photovoltaic (PV) applications that reduces the number of components, voltage stress, and overall size and cost. Enhanced incremental maximum power point tracking (EINC-MPPT) is used in the PV standalone system to offer a fast dynamic response, track maximum power, and regulate the PV module output voltage. This paper presents a PV-boost DC–DC single-input multi-output (SIMO) converter linked to solar panels to provide supply voltage to the inverter. A level-shifted constant multicarrier sinusoidal pulse width modulation (LSCMSPWM) technique is used to produce a better-synthesized output waveform from the MLI, resulting in low total harmonic distortion (THD) and also meeting IEEE standards. The suggested MLI is simulated in MATLAB/Simulink and tested with a hardware prototype under various load conditions. It is suitable for medium-power and grid-connected renewable energy systems applications. The qualitative and quantitative parameters of the proposed MLI have been evaluated by cost function (CF), number of components, reliability, THD, and total standing voltage (TSV); these parameters are compared with the existing MLIs.